Identifying Factors to Increase the Adoption of Integrated Pest Management Practices: An Audience Segmentation Study - John M. Diaz; Laura A. Warner; Faith M. Oi (Journal of International Agricultural and Extension Education, 2020)
Tailoring programs based on audience needs and priorities is a critical component of effective programs. Audience segmentation research provides an opportunity to identify subgroups based on characteristics that affect their willingness to adopt a certain behavior and allows extension programs to fulfill a variety of needs and target the most important groups within a population. Currently there is minimal research exploring the factors that influence the sustained adoption of environmentally responsible pest management practices. As a result, the purpose of this study was to explore potential extension audience segmentation strategies by evaluating factors related to differences in residents’ intentions to use integrated pest management (IPM) practices.We used online surveys to collect data from a sample of 3,588 residents. We found relatively high intentions to adopt IPM practices but there remains room to increase adoption levels. Responses of undecided ranged from 14.7% to 23.1% across all pest management practices, which demonstrates the potential for an audience to be influenced to adopt an IPM approach. We also found that demographics, complementary conservation behaviors and engagement with the natural environment characterize meaningful subgroups to guide extension program design. Interestingly, we found an interrelationship between the intention and actual adoption of other environmentally responsible practices and the intention to adopt IPM practices. Respondents with greater intent to engage in IPM were also more engaged in general conservation, water conservation and fertilizer best practices. This demonstrates that previous engagement with other environmentally responsible practices may influence the adoption of IPM. Respondents with greater intent to engage in IPM also had less negative experiences with water quality and availability, implying the possible role negative consequences can play as teaching tools in extension program.
Keywords: audience segmentation; pest management; practice adoption; integrated pest management; water quality; water quantity